Linsitinib inhibits proliferation and induces apoptosis of both IGF-1R and TSH-R expressing cells - Luffy, Maximilian; Ganz, Anna-Lena; Wagner, Stefanie; Wolf, Jan; Ropertz, Julian; Zeidan, Ryan; Kent, Jeffrey D.; Douglas, Raymond S.; Kahaly, George J. (Frontiers in Immunology, 2024)
BackgroundThe insulin-like growth factor 1 receptor (IGF-1R) and the thyrotropin receptor (TSH-R) are expressed on orbital cells and thyrocytes. These receptors are targeted in autoimmune-induced thyroid eye disease (TED). Effective therapeutic treatment of TED inhibits activation of the IGF-1R/TSH-R complex.MethodsThe inhibitory effect on cell proliferation of a small molecule targeting IGF-1R phosphorylation (Linsitinib) was investigated in an IGF-1R expressing cell line and a Chinese Hamster Ovary (CHO) cell line overexpressing TSH-R. An IGF-1R monoclonal antibody antagonist, Teprotumumab served as control. Both cell lines were plated in a 96-well format and treated with both compounds for 24 hours. After addition of tetrazolium, absorbance was measured. The apoptosis marker caspase-3/7 activity was measured. The half-maximal inhibitory concentration (IC50) of TSH-R-Ab induced stimulation (stimulatory monoclonal antibody, mAb, M22) of the TSH-R cell line was evaluated with a cell-based bioassay for blocking TSH-R-Ab. Cells were treated with ten rising concentrations of either Linsitinib, Linsitinib + Metformin, Teprotumumab, or a blocking TSH-R mAb (K1-70).ResultsLinsitinib strongly inhibited the proliferation of both cell lines at several concentrations: 31,612.5 ng/mL (IGF-1R cell line -78%, P=0.0031, TSH-R cell line -75%, P=0.0059), and at 63,225 ng/mL (IGF-1R cell line -73%, P=0.0073, TSH-R cell line -73%, P=0.0108). Linsitinib induced apoptosis of both cell lines, both morphologically confirmed and with an increased caspase-3/7 activity at concentrations of 31,612.5 ng/mL (IGF-1R cell line P=0.0158, TSH-R cell line P=0.0048) and 63,225 ng/mL (IGF-1R cell line P=0.0005, TSH-R cell line P=0.0020). Linsitinib markedly inhibited proliferation of the IGF-1R cell line at all concentrations compared to Teprotumumab (P=0.0286). Teprotumumab inhibition was significant only at 15,806.25 ng/mL with the TSH-R cell line (-15%, P=0.0396). In addition, in the TSH-R-Ab blocking bioassay, Linsitinib and the tested compounds demonstrated strong inhibition across all ten dilutions (100%).ConclusionsLinsitinib effectively induces apoptosis and inhibits proliferation of both IGF-1R and TSH-R expressing target cells, therefore demonstrating its therapeutic potential to block the reported crosstalk of the two mediators in autoimmune TED.